Abortion in Malaysian Law: a comparative study with Islamic jurisprudence - Muhammad Husni, Ahmad; Mohammad, Abdul Basir; Mohd Nor, Amir Husin; Laluddin, Hayatullah; Samuri, Mohd. Al Adib (American-Eurasian Network for Scientific Information, 2013)
This study aims to address abortion between Malaysian law and Islamic jurisprudence which will look into Malaysian law to extract ruling on abortion, and at the same time trying to know the ruling on abortion in light of Islamic jurisprudence by taking advantage of scattered issues mentioned by scholars and jurists on this subject. The study will then identify areas of agreement and differences between Malaysian law and Islamic jurisprudence. The study will also discuss the negative effects left by abortion in Malaysian society in particular.The study adopted inductive approach to collect the information in Malaysian law and Islamic jurisprudence in this regard and followed by an analytical study to understand the texts contained in the Malaysian law and Islamic jurisprudence and also compared them to identify the similarities and dissimilarities between jurisprudence and law. The study discussed the historical dimension of abortion in search of the roots and origins of this dilemma in order to develop solutions. The study reached to some results the most important ones are that: The Malaysian law prevents abortion except in cases of necessity and when there is an acceptable excuse. Furthermore, the scholars differed in ruling on abortion before the fetus starts breathing (before four months) but they are consensus on its prohibition when the fetus starts breathing.